CCAFS Flagship 2: Climate Services and Safety Nets Science Meeting - Jordan, Pamela (2017)
CCAFS Flagship 2: Climate Risk Management (presently CCAFS Flagship 4: Climate Services and Safety Nets) held a Science Meeting for all project leaders under Flagship 2 at the International Research Institute for Climate and Society in Palisades, New York in October 2016. The goal of the workshop was to give the project leaders the chance to share their work and learn about each other’s projects. The group discussed how best to collaborate and plans for flagship moving into Phase II. The meeting proved to be a useful opportunity for collaboration and knowledge sharing across projects. The presentations – from summaries of work to cross-cutting discussions – gave participants the opportunity to discuss cross-project fertilization, how to improve their projects, and how to improve collaboration across the flagship. Such discussions and subsequent activities will help the flagship reach its intended outputs and outcomes. Project leaders were able to learn from each other as well as gain valuable insight into seasonal forecasting from Dr. Lisa Goddard. The participants found the relationship building and information presented in the meeting valuable, and many plans were put in place for continued collaboration.